Serratula baetica Boiss. subsp. lusitanica (Asteraceae) subsp. nova - Cantó, Paloma (Lazaroa, 1982)
Se describe un nuevo taxon para Portugal: Serratula baetica Boiss. subsp. lusitanica Cantó, subsp. nova.